2015
DOI: 10.1167/iovs.14-15741
|View full text |Cite
|
Sign up to set email alerts
|

Space Perception of Strabismic Observers in the Real World Environment

Abstract: Locating a single target on the ground is sufficient with monocular depth information, but binocular depth information is required when the target is suspended in midair. Since the absolute binocular disparity information of the single target is weak beyond 2 m, we suggest the visual system localizes the single target using the relative binocular disparity information between the midair target and the visible ground surface. Consequently, strabismic observers with residual stereopsis localize a target more acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 54 publications
3
32
0
Order By: Relevance
“…In our display, the horizontal ground plane would be occluded up to a distance of 15 m. This is perhaps the most likely explanation. J. J. Gibson ( 1950 ), and others (Gillam, 1995 ; Meng & Sedgwick, 2001 ; Ooi et al, 2015 ; Wu, Zhou, Shi, He, & Ooi, 2015 ), have suggested (or shown) that the ground plane and surface contact relations are important for judging absolute distance and relative distance intervals. This may well underlie the elevation of monocular thresholds at near distances, although it is still uncertain how findings about absolute distance translate to distance discrimination thresholds.…”
Section: Discussionmentioning
confidence: 99%
“…In our display, the horizontal ground plane would be occluded up to a distance of 15 m. This is perhaps the most likely explanation. J. J. Gibson ( 1950 ), and others (Gillam, 1995 ; Meng & Sedgwick, 2001 ; Ooi et al, 2015 ; Wu, Zhou, Shi, He, & Ooi, 2015 ), have suggested (or shown) that the ground plane and surface contact relations are important for judging absolute distance and relative distance intervals. This may well underlie the elevation of monocular thresholds at near distances, although it is still uncertain how findings about absolute distance translate to distance discrimination thresholds.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous psychophysical studies have shown that perceived binocular depth can be affected by a common surface (McKee, 1983; Glennerster and McKee, 1999; He and Ooi, 2000). Importantly, a recent result shows that perceived absolute distance to objects on the ground surface is not different between monocular and binocular viewing conditions (Ooi and He, 2015). Binocular disparity may only play a critical role in perceiving absolute distance of a target in midair.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, the shape of the hand is wider and less accurate when reaching and grasping, and the time taken for the reach is much slower in individuals where stereopsis is reduced or absent in adults [ 11 14 ], with even larger errors in these tasks for children with reduced stereoacuity [ 15 17 ]. Poor depth perception can also impact upon gross motor skills such as walking; adults with reduced stereoacuity also demonstrate differences in gait with a more cautious approach, higher toe clearance, and increased hesitation [ 18 , 19 ]. All of these skills may have implications for the likelihood of taking part in team, motor, and social activities; however, this relationship has rarely been studied.…”
Section: Introductionmentioning
confidence: 99%